Exploring the determinants of online health service usage intentions under the threat of air pollution - Xueru Xu; Tao Wang; Chuang Liu; Chuang Liu; Li Luo; Xiaofei Liu (Frontiers Media S.A., 2024)
IntroductionThe rapid evolution of online health services (OHS) has significantly improved healthcare accessibility. However, the impact of air pollution on individuals' willingness to engage with OHS remains underexplored in the existing literature. This study addresses this gap by investigating how air pollution threats influence the intention to use OHS, grounded in Protection Motivation Theory (PMT) and Rational Choice Theory (RCT).MethodsUsing cross-sectional survey data, a theoretical model was developed and tested to examine the relationships between threat appraisal, coping appraisal, perceived benefits, perceived costs, and OHS usage intentions.ResultsThe findings indicate that threat appraisal, coping appraisal, and perceived benefits positively affect the intention to use OHS, while perceived costs negatively impact usage intention. Additionally, age significantly moderates the relationship between coping appraisal and the intention to use OHS.DiscussionThis study extends the application of PMT and RCT in the context of OHS. It provides valuable insights into the factors influencing users' intentions to utilize these services, with implications for improving OHS adoption in environments affected by air pollution.